Implications of using systematic decomposition structures to organize building LCA information: A comparative analysis of national standards and guidelines- IEA EBC ANNEX 72. Issue 2 (November 2020) - Soust-Verdaguer, B; García Martínez, A; Llatas, C; Gómez de Cózar, J.C.; Allacker, K; Trigaux, D; Alsema, E; Berg, B; Dowdell, D; Debacker, W; Frischknecht, R; Ramseier, L; et al.
Abstract: Introduction: The application of the Life Cycle Assessment (LCA) technique to a building requires the collection and organization of a large amount of data over its life cycle. The systematic decomposition method can be used to classify building components, elements and materials, overcome specific difficulties that are encountered when attempting to complete the life cycle inventory and increase the reliability and transparency of results. In this paper, which was developed in the context of the research project IEA EBC Annex 72, we demonstrate the implications of taking such approach and describe the results of a comparison among different national standards/guidelines that are used to conduct LCA for building decomposition. Methods: We initially identified the main characteristics of the standards/guidelines used by Annex participant countries. The "be2226" reference office building was used as a reference to apply the different national standards/guidelines related to building decomposition. It served as a basis of comparison, allowing us to identify the implications of using different systems/standards in the LCA practice, in terms of how these differences affect the LCI structures, LCA databases and the methods used to communicate results. We also analyzed the implications of integrating these standards/guidelines into Building Information Modelling (BIM) to support LCA. Results: Twelve national classification systems/standards/guidelines for the building decomposition were compared. Differences were identified among the levels of decomposition and grouping principles, as well as the consequences of these differences that were related to the LCI organization. In addition, differences were observed among the LCA databases and the structures of the results. Conclusions: The findings of this study summarize and provide an overview of the most relevant aspects of using a standardized building decomposition structure to conduct LCA. Recommendations are formulated on the basis of these findings.